Babesia microti seroprevalence in Minnesota blood donors. Issue 8 (12th November 2012) - Tonnetti, Laura; Thorp, Aaron M.; Deisting, Barbara; Bachowski, Gary; Johnson, Stephanie T.; Wey, Andrew R.; Hodges, James S.; Leiby, David A.; Mair, David
<x xml:space="preserve">Abstract</x> Background The increasing frequency of transfusion‐transmitted babesiosis represents a concern for the safety of the US blood supply. The agent responsible for the disease, the intraerythrocytic parasite Babesia microti, is naturally transmitted to humans by a tick bite and is endemic in areas of the Northeast and Upper Midwest United States. In this study, we explored B. microti seroprevalence in blood donors from different areas of Minnesota (MN). Study Design and Methods We tested 2150 blood donors in MN for the presence of antibodies against B. microti using an immunofluorescent assay (IFA). Donors identified as positive (≥64) were also tested by real‐time polymerase chain reaction (PCR) for the presence of parasite DNA. Seropositive donors were contacted by phone and asked questions regarding tick exposure. Donors positive by IFA were indefinitely deferred from donating blood. Results A total of 2150 donations were tested between October 2010 and November 2011. Forty‐two donors (2.0%) were positive by IFA and one was also PCR positive. All positive donors reported extended outdoor activities, 12 recalled finding ticks on their body, and six had flu‐like symptoms since their last blood draw. Conclusions This study provides new data about B. microti seroprevalence in MN blood donors. Possibly because the targeted collection areas were mostly expected to be endemic for the parasite, the observed seroprevalence levels were higher than expected, although the geographic distribution of positive donors did not completely overlap with the distribution of reported clinical cases in MN.